Analysis of Influence of Disturbing Signals Caused by Rail Magnetization to a Cab Signaling System - Augutis, V.; Gailius, D.; Misevičius, R.; Pronko, V. (Elektronika ir Elektrotechnika, 2010)
A cab signaling system is used to transfer traffic-light signals to a cab. The signaling signals are magnetic field signals measured by a pick-up coil of a cab. A reception of informative signals is often disturbed by permanent magnetization of rails that occur due to different factors. In this article influence of such disturbing signals is described and their influence to signal reception system is analyzed. Different effects of disturbances to the detection of signaling signals are analyzed in subject to signaling signal frequency, cab speed and other factors.